• Asignatura: Matemáticas
  • Autor: estivenelmono
  • hace 8 años


reempazar \: y \: luego \: resolver   \: reemplazadores \:  \:   a = 2 \:  \: b = 5 \:  \: c =  - 3 \:  \: d =  - 1 \:  \: f = 0 \\   \\ 5 {a }^{2} - 2bc - 3d \\  \\ 4ab - 3bc - 15d \\  \\ 6 {a}^{3}f \\  \\ 2 {a}^{2}  -  {b}^{3}  -  {c}^{1}  -  {d}^{5}  \\  \\ 3(a - b) + 2 \: (c - d) \\  \\  \frac{c}{3} +  \frac{b}{5}  -  \frac{a}{2}  \\  \\ (b + \: {c}^{2})

Respuestas

Respuesta dada por: sonia2302
4

Explicación paso a paso:

 1)5 {a}^{2}  - 2bc - 3d =  \\( 5 \times  {2}^{2} )- (2 \times 3 \times ( - 5)) - (3 \times ( - 1)  \\ (5 \times 4) - ( - 30) - ( - 3)\\ 20 + 30 + 3 = 53\\  \\  2)4ab - 3bc - 15d = \\(4 \times 2 \times 3) - (3 \times 3 \times ( - 5)) - (15 \times ( - 1)) \\ 24 - ( - 45) - ( - 15) \\ 24 + 45 + 15 = 84  \\  \\ 3) 6 {a}^{3}  =  \\6 \times  {2}^{3} = 6 \times 8 = 48   \\ \\ 4) 2 {a}^{2}  -  {b}^{3}  -  {c}^{1}  -  {d}^{5}  = \\(4 \times  {2}^{2}) - ( {3}^{3}  ) - ( -  {5}^{5} ) \\ (4 \times 4) - 27 - ( -3125) = 3114 \\   \\ 5)  3(a - b) + 2(c - d) = \\3(2- 3) + 2(-5 - (-1)) = \\   3(-1) + 2(-5+1) = \\ -3 + 2(-4) = \\  -3 + (-8) = -11 \\ \\ 6) \frac{-5}{3}  +  \frac{3}{5}   -   \frac{2}{2}  =    \frac{-50+18-30}{30}=   \frac{-62}{30}\\ \\simplficamos y queda -31/15\\ \\ =    \frac{-62}{30}\\7) \: (b +  {c}^{2} ) =(3+(-5) +( {-5})^{2} ) = (3-5 +25 ) =23

Preguntas similares